Eye sore - Jackson, Melanie, 1956- (Orca currents., 2015)
"The last thing Chaz wants to do is spend his summer working on his father's Eye, a Ferris wheel set up to view scenic North Vancouver. For one thing, Chaz would rather pursue his own passion: dance in the style of Gene Kelly. More important, Chaz suffers from vertigo, and even the thought of the Eye makes him want to lose his lunch. But when angry protesters and a mysterious vandal threaten his father's dream Chaz has to pull it together or his family will lose everything"--Back cover.